Diferença como relação: leituras contemporâneas de Heráclito - Ferronatto, Mariza Ardem Scipioni Vial (2009)
The proposal of this work has as conducting wire the inquiry of the following question: how it is possible that the notion of difference, present on the Heraclitu's fragments, can, at the same time, underlie an ontic sense of world, like the conceived by Nietzsche, and the ontologic sense of world, conceived by Heidegger? The reading of the selected bibliography indicates the possibility of exploration of the hypothesis that, as readers of Heraclitus, Nietzsche and Heidegger agree when identifying the difference as relation; however, they diverge when it refers to the dimension in wich this relation effectively happen. With the objective to underlie the hypothesis proposed, the work was divided in three distinct stages, but related. The first chapter dedicates to analyze the heideggerian reading of the fragments 16, 123, and 51 (DK) of Heraclitus. Taking as starting point these three fragments, it intendes to clarify the direction of the reading and the Heidegger's intention when approaching them. The second chapter intends to point the heraclitian theories present in the nietzschian thought and to elucidate this relation through an interpretative analysis of the Nietzsche's texts where this relation makes itself present. The third chapter aims to demonstrate that Heidegger and Nietzsche find in Heraclitus a central fundamental concept: the question of the difference seen as relation, that is used by both as essential nexus for explicitation of his theories. To conclude, it makes a reevaluation of the dimension where the use of the notion of difference as relation effectively happen.